Deformation and swelling of coal induced from competitive adsorption of CH4/CO2/N2. (15th February 2021) - Li-wei, Chen; Lin, Wang; Tian-hong, Yang; Hong-min, Yang
Highlights: The swelling of coal was calculated via molecular simulation. The influence of pressure on swelling was clarified. The swelling under geological conditions was discussed. Abstract: The deformation and swelling coal macromolecules could be induced from the adsorption of the CH4, CO2, and N2, however, their microscopic mechanisms have been minimally reported to date. Here, the binary competitive adsorption and the induced differential swelling ratio of the coal matrix were simulated through the molecular simulation and the poromechanical model. The swelling ratios of coal matrix in CO2 + CH4 competitive systems increase with the increasing CO2 mole fraction. However, those in the N2 + CH4 competitive systems decrease with the increasing N2 mole fraction. The swelling of the coal matrix is more significant at the high pressures than at the low pressures. The reduction rates are higher at N2 mole fraction of 0.4–0.8 than those at N2 mole fraction of 0–0.4 and 0.8–1.0. Under the geological conditions, almost half of the differential swelling ratios could be achieved for CO2 mole fraction of 0.25 and CH4 mole fraction of 0.40 respectively independent of the burial depth. These two differential swelling ratios increase with the increasing burial depth. Our results indicated that the swelling effects are significant at the shallowest sites (especially at the injection sites > 1200 m), leading to the low permeability for the deep ECBM engineering.